Effect of tumor burden and growth rate on treatment outcomes of nivolumab in head and neck cancer - Suzuki, C.; Kiyota, N.; Imamura, Y.; Rikitake, J.; Sai, S.; Koyama, T.; Hyogo, Y.; Nagatani, Y.; Funakoshi, Y.; Toyoda, M.; Otsuki, N.; Nibu, KI; et al. (International journal of clinical oncology, 2020)
Background Nivolumab improves overall survival (OS) in patients with platinum-refractory recurrent and metastatic head and neck squamous cell carcinoma (R/M HNSCC). In one study, however, Kaplan–Meier OS and progression-free survival (PFS) curves for the nivolumab and cytotoxic agent arms crossed at 3–6 months, suggesting that patients with initial resistance to immunotherapy might have better outcomes with cytotoxic treatment. Here, we explored the conditions and candidates which are predictive of nivolumab outcomes in R/M HNSCC. Methods We retrospectively reviewed the clinical records of 27 consecutive R/M HNSCC patients treated with nivolumab from 2014 to 2018. Tumor size was evaluated by RECIST ver.1.1. Tumor growth rate (Gr) was defined as 3 log(D 0 /D pre )/t , where D 0 and D pre are the sum of the diameters of the target lesions (SumTLs) at baseline and pre-baseline, and t is time, with 1 t defined as 4 weeks. Results Twenty-five patients were enrolled. Survival was significantly worse in patients with disease progression within 3 months. Outcomes appeared poorer in patients with higher pre-treatment Gr and bigger SumTLs at baseline. We therefore explored the association between prognosis, Gr and SumTLs. Recursive partitioning analysis showed that the characteristics of patients with disease progression after 3 months were Gr < 0.76 and SumTLs < 31.0 mm. Further, Gr < 0.76 and SumTLs < 31.0 mm was associated with significantly longer PFS ( p = 0.01) and OS ( p < 0.01). Conclusions These results suggest that Gr and SumTLs at baseline are significantly associated with OS and PFS in R/M HNSCC patients treated with nivolumab.